The english language needs of aircraft maintenance engineering students at a private college / Thevarajah T. Ratnam - T. Ratnam, Thevarajah (2012)
This research report attempts to identify the English language needs of the students of the Diploma in Aircraft Maintenance Technology at Kolej TAFE Seremban. The study first discusses the importance of English in aircraft maintenance engineering and the English language proficiency of Malaysian students at present. This is followed by a review of related literature. A questionnaire was used to employ feedback from a sample of 100 students while five lecturers were interviewed individually. The findings show that students generally feel they have the required level of proficiency in English to complete the course successfully. However, the lecturers feel that the students still lack reading and writing skills, especially writing reports. The study indicates that the students would benefit from the introduction of two English language modules. The first would be an English for General Purposes (EGP) module that incorporates the four language skills, while the second would be English for Specific Purposes (ESP) course with learning material sourced from texts related to aircraft maintenance engineering.